Morality in the flesh: on the link between bodily self-consciousness, moral identity and (dis)honest behaviour - Marina Scattolin; Maria Serena Panasiti; Salvatore Maria Aglioti (Royal Society Open Science, 2022)
The sense of owning a body (ownership) and controlling its actions (agency) are two main pillars of bodily self-consciousness (BSC). Although studies suggest that BSC signals and morality may be associated, whether such association has a positive or negative direction remains unclear. To investigate this issue, we conducted two pre-registered, online studies, in which a total of 1309 participants completed BSC- and morality-related questionnaires and undertook a task where they could cheat for monetary gain. We found that participants with high sense of ownership displayed high moral identity, which supports the notion that ownership is used to associate the self with positive characteristics. Moreover, high agency was associated with increased moral identity when sense of power is high. Results regarding deception are less clear, and might relate to the impact of COVID-19. Our results concerning moral identity may inspire policies that rely on changes of corporeal awareness to contrast immorality.